Interaction on Ice Tea's Political Social Media Accounts: The Social Context of Power (Cyberpragmatig) - Pheni Cahya Kartika; Idhoofiyatul Fatin; Ngatmain Ngatmain (Universitas Muhammadiyah Malang, 2025)
This study aims to analyze the social context in video uploads on social media accounts (YouTube and Instagram) regarding the case of Gus Miftah and the Iced Tea Seller and to apply the theory of power to strengthen the social context. The primary focus of this research is to identify and explain how the uploads will be interpreted in terms of constructs and interpretations studied in cyberpragmatics. The method used in this research is descriptive qualitative analysis by examining eight uploads from YouTube and Instagram in December 2024. The results showed that the uploads that appear in the 8 data besides showing the meaning of the construct and the meaning of interpretation as a cyberpragmatic study, which relates to the power relation of power consisting of reward power, expert power, estimated power, referent power, and coercive power as a measuring material for the existence of power in the social context. These findings enrich the study of pragmatics, especially cyberpragmatics in Indonesia, and provide insight into language studies on social media and other fields of science that support each other.